Fetal bradycardia associated with left ventricle noncompaction diagnosed as HCN4 mutations - Kosuke Yonehara (Annals of Pediatric Cardiology)
A 35-year-old pregnant woman was referred to our hospital because of fetal bradycardia. Fetal echocardiography revealed a normal fetal heart except for slightly prominent trabeculae in the left ventricle, normal cardiac function, and fetal sinus bradycardia with a heart rate of 100 bpm. Electrocardiography (ECG) after birth revealed sinus bradycardia with a heart rate of 70–80 bpm. Transthoracic echocardiography revealed left ventricular noncompaction localized in the apex with normal cardiac function. A 24-h Holter ECG showed a heart rate range of 62–169 bpm without a pause of more than 2 s. A genome analysis performed during the neonatal period revealed a heterozygous inflame variant p.(Ser672_Asp676del)[chr15:g. 73324203_733242] in HCN4 gene. Fetuses with a heart rate less than the 3rd percentile of the gestational age should be followed and screened for congenital heart disease and cardiomyopathy. In addition, inherited arrhythmia syndrome should be considered.